Related Party Transactions, Supply chain and Cost Management on Firm’s Value: Evidence from Indonesia - Amrie Firmansyah; Aji Kusumo Ardi (International Journal of Supply Chain Management, 2020)
Abstract. Firms are involved in supply chains to achieve operative efficiency, develop strategic advantages, and generate financial profits. This study aims to examine the effect of disclosure of Related Party Transactions (RPT), the disclosure of supply chain and cost management on a firm’s value. The firm’s value is considered necessary because a high level of shareholder prosperity will follow the big firm's value. Also, supply chain management, as an agent of the company, seeks to increase the firm’s value, which is reflected in the stock market price of the companies. This research is quantitative research with multiple linear regression models. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange (ISE). The type of data used in this study is secondary data in the form of financial statements and annual reports from 2014 to 2016. The sample selection using a purposive sampling method with the number of samples amounted to 255 samples. This study uses data with the same number of years for three years, so that this research is research with panel data. The results of this study suggest that the RPT disclosure and the supply chain management have a positive effect on the firm’s value. Earnings management based on current discretionary proxies used in this study indicates that investors do not use cost information to make investment-related decisions. To confirm the results of this study, further research is expected to use longer years.